Unveiling the Impact of AI-Driven Marketing on Customer Experience and Purchase Intention: A Systematic Literature Review Using Python-Based Bibliometric Analysis - Agustina, Dewi Ayu; Arifah, Ika Diyah Candra (Journal of Digital Business and Innovation Management, 2025)
The integration of Artificial Intelligence (AI) in marketing has gained momentum as businesses seek to enhance customer experience and drive purchase intention. This study presents a systematic literature review (SLR) using Python-based bibliometric tools to analyze recent scholarly contributions from 2015 to 2025. By extracting and analyzing data from Scopus and Web of Science databases, we identify thematic trends, key contributors, and knowledge gaps in AI-driven marketing literature. Findings reveal a strong emphasis on personalization, customer engagement, and trust as mediators between AI applications and purchase intention. This paper provides a conceptual foundation for future empirical and experimental studies in AI marketing.